LL37 Inhibits Aspergillus fumigatus Infection via Directly Binding to the Fungus and Preventing Excessive Inflammation - Luo, Xiao-Li; Li, Jian-Xiong; Huang, Hua-Rong; Duan, Jie-Lin; Dai, Ruo-Xuan; Tao, Ru-Jia; Yang, Ling; Hou, Jia-yun; Jia, Xin-Ming; Xu, Jin-Fu (Frontiers in Immunology, 2019)
The incidence of Aspergillus fumigatus infection and the rate of resistance to antifungal drugs have sharply increased in recent years. LL37 has been reported as a host defense peptide with broad-spectrum antibacterial activities. However, the role of LL37 during A. fumigatus infection remains unclear. Here, we examined the interaction between LL37 and A. fumigatus and found that synthetic LL37 could directly bind to the surface of A. fumigatus, disrupting the integrity of the cell wall in vitro. LL37 inhibited mycelial growth in a concentration-dependent manner, rather than fungicidal effect even at high concentration (e.g., 20 μM). Interestingly, low concentrations of LL37 (e.g., 4 μM) significantly attenuated mycelial adhesion and prevented the invasion and destruction of epithelial cells. Following LL37 treatment, the levels of proinflammatory cytokines released by A. fumigatus-stimulated macrophages decreased significantly, accompanied by downregulation of M1 type markers. In a mouse model of pulmonary A. fumigatus infection, LL37-treated mice showed lower amounts of fungi load, moderate pathological damage, and reduced proinflammatory cytokines. Further, LL37 transgenic mice (LL37+/+) were examined to investigate the effects of endogenous LL37 in an A. fumigatus infection model and showed lower susceptibility to A. fumigatus infection in comparison with wild-type mice. In addition, LL37 also played a protective role in an immunosuppressed mouse model of A. fumigatus infection. Thus, LL37 inhibits A. fumigatus infection via directly binding to mycelia and reducing excessive inflammation. LL37 or its analogues may therefore constitute potential drug components for A. fumigatus infection.